Research and Application of Intelligentizing Technology for Rail Traffic Equipment - DING Rong-jun; YANG Wei-feng; TANG Jun (机车电传动)
Concept and system structure of rail traffic equipment intelligentizing were presented, technic base and application of which was summarized, at the same time, development of it was prospected.